A critical review on bubble dynamics parameters influencing boiling heat transfer. (October 2017) - Mohanty, Rajiva Lochan; Das, Mihir Kumar
Abstract: The rate of heat transfer during boiling is governed by various bubble dynamics parameters such as bubble departure diameter, active nucleation site density, bubble waiting period, bubble growth period, bubble growth rate and bubble departure frequency. The study of bubble dynamics during boiling of liquids over a heated surface is a complex process due to non-linear growth of bubbles. Many studies on bubble dynamics is carried out by both experimentally and numerically. These studies are carried to propose various empirical and semi-empirical correlations for determination of bubble dynamics parameters. In the present paper, a comprehensive review is carried out to compile various correlations proposed for determination of bubble dynamics parameters. The correlation for determination of boiling heat flux or boiling heat transfer coefficient based on these bubble dynamics parameters are reported. This is done to identify important bubble dynamics parameters affecting boiling heat transfer process. Further, factors affecting bubble dynamics parameters such as effect of thermo-physical properties, heat flux, liquid sub-cooling, wall superheat, contact angle, gravity, cavity spacing and pressure are also given to get an insight into the correlation proposed for determinations of bubble dynamics parameters. The present review article proposes the importance of development of generalized boiling heat transfer correlation using bubble dynamics parameters.